New managers for changing global economy: Comparative analysis of business education by Ukrainian students in home universities and abroad - Hlynskyy, Nazar; Karyy, Oleh; Yasevych, Anastasia (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The article presents the analysis of causes stimulating Ukrainian students of managerial studies to emigrate abroad in search of other places of education. Factors that influence the process of integration of Ukrainian youth in the international environment are analyzed and directions of activities for overcoming the negative trends in the area are proposed. As part of the research the level of participation of Ukrainian students − future managers, economists, and entrepreneurs − in international exchange programs is also examined. An important dimension of the study is to determine the expectations of Ukrainian students about the prospects of a career abroad and a comparison with the assessment of such prospects in Ukraine. The results of a comparative analysis of the structure of the assessment of employment opportunities for students studying abroad and in Ukraine have been presented. The level of perception of the main differences between the educational process in Ukraine and abroad by the test group has been determined. Recommendations relating to the problems identified and directed to the reform of higher business education in Ukraine have been made
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2017; Nr 463; s. 285-296
Keywords: managerial studies; emigration; integration of Ukrainian youth in the international environment; studia menedżerskie; emigracja; integracja ukraińskiej młodzieży ze środowiskiem międzynarodowym